2017
DOI: 10.21275/art20163944
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension among Faculty Members of Health Sciences College at South Saudi Arabia: Prevalence and Risk Factors

Abstract: Background: Essential Hypertension is a challenge for public health professionals all over the world. The aims of the present study were to determine the prevalence of hypertension among faculty members of private College and to investigate risks factors. Methods: A cross-sectional study was conducted in a private College-Saudi Arabia. The sample size was 115 members. The participants were asked to complete a self-reported questionnaire. Results: Both systolic and diastolic hypertension were significantly asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(26 reference statements)
0
0
1
Order By: Relevance
“…The results of the current study also showed that the prevalence of hypertension and diabetes is lower than the prevalence in a study conducted in Palestine aimed to determine the prevalence of cardiovascular disease and associated risk factors in the population of Gaza strip, where the prevalence rates were (28.4%,19.1% respectively) while heart disease prevalence was lower than in our study (8.3% compared with 12.6%) [31] Moreover, the prevalence of HTN is lower than the prevalence in two studies conducted in Swaziland and Saudi Arabia where the prevalence rates were (48.3% ,39.2% respectively) [3,32].This variation according to Alshloul who indicated that those had higher education levels (such as doctorate and master holders) had less vulnerability to develop HTN and are the more knowledgeable and the more aware concerning healthy lifestyle and HTN associated risk factors [32] A recent study conducted in Jordan aimed to investigate the prevalence of obesity among Jordanian women and its association with a wide range of chronic diseases. The results indicated that 59.8% of the study population had arthritis pain.…”
Section: Discussioncontrasting
confidence: 64%
“…The results of the current study also showed that the prevalence of hypertension and diabetes is lower than the prevalence in a study conducted in Palestine aimed to determine the prevalence of cardiovascular disease and associated risk factors in the population of Gaza strip, where the prevalence rates were (28.4%,19.1% respectively) while heart disease prevalence was lower than in our study (8.3% compared with 12.6%) [31] Moreover, the prevalence of HTN is lower than the prevalence in two studies conducted in Swaziland and Saudi Arabia where the prevalence rates were (48.3% ,39.2% respectively) [3,32].This variation according to Alshloul who indicated that those had higher education levels (such as doctorate and master holders) had less vulnerability to develop HTN and are the more knowledgeable and the more aware concerning healthy lifestyle and HTN associated risk factors [32] A recent study conducted in Jordan aimed to investigate the prevalence of obesity among Jordanian women and its association with a wide range of chronic diseases. The results indicated that 59.8% of the study population had arthritis pain.…”
Section: Discussioncontrasting
confidence: 64%